The Impact of Rebranding on Indrive User Trust Among Students in Greater Bandung - Azhara, Rifa Ralinda; Primasari, Intan (Jurnal Ilmiah Komunikasi Makna, 2025)
This study aims to investigate the impact of the rebranding efforts undertaken by Indrive on customer trust, particularly among students in the Bandung Raya area. A total of 102 students, who are active users of the Indrive application, participated in this research by completing a questionnaire. A quantitative method was employed, with descriptive-verification analysis through Hypothesis Testing (T-test and F-test). The collected data indicates that the change in logo has a significant impact, with 71.96% of respondents showing a positive response to the rebranding. The primary findings of this study suggest that the rebranding of Indrive has a tangible influence on customer trust, especially among students in the Bandung Raya area. Data analysis reveals that 7.82% of the changes in customer trust can be directly attributed to the rebranding. The remaining 2.18% is attributed to other unrelated factors. These results indicate that the visual changes and brand messaging conveyed through the rebranding successfully affect customer perceptions and trust. Thus, this study confirms that the rebranding of Indrive has a significant impact on strengthening customer trust among students in the Bandung Raya area.